2021
DOI: 10.1021/acs.chemmater.1c01421
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Copper Iodide-Based Inorganic–Organic Hybrid Semiconductors: Synthesis, Structures, and Optical and Transport Properties

Abstract: A group of copper iodide based hybrid semiconductors with the general formula of 2D-CuI(L) 0.5 (L = organic ligands) are synthesized and structurally characterized.All compounds are two-dimensional (2D) networks made of one-dimensional (1D) copper iodide staircase chains that are interconnected by bidentate Nitrogen containing ligands. Results from optical absorption and emission experiments and density functional theory (DFT) calculations reveal that their photoluminescence (PL) can be systematically tuned by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 41 publications
1
39
0
Order By: Relevance
“…These compounds are air- and water-stable. It has been demonstrated that the thermal stability of copper­(I) iodide hybrids depends on their dimensionality, and the overall trend is 0D < 1D < 2D. , The decomposition temperature for 0D and 1D copper­(I) iodide hybrids is typically 50–150 °C. , Compounds 1 – 10 with 0D/1D structures are expected to have similar thermal stability. The hybrid copper iodide compounds presented here cover a wide variety of structural types.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds are air- and water-stable. It has been demonstrated that the thermal stability of copper­(I) iodide hybrids depends on their dimensionality, and the overall trend is 0D < 1D < 2D. , The decomposition temperature for 0D and 1D copper­(I) iodide hybrids is typically 50–150 °C. , Compounds 1 – 10 with 0D/1D structures are expected to have similar thermal stability. The hybrid copper iodide compounds presented here cover a wide variety of structural types.…”
Section: Resultsmentioning
confidence: 99%
“…They are ideal candidates for better‐performing lighting materials containing no rare‐earth metals, as well as promising alternative materials for luminescent noble metal Ir(III), Pt(II), Os(II) complexes given the low price, minor environmental pollution, and abundant resource of copper. [ 1–13 ] Owing to the rich coordination chemistry of Cu(I) ions, their combination with organic and inorganic ligands often leads to a large structural diversity, ranging from discrete molecular 0D to 1D chains, and from 2D layers to extended 3D networks. [ 14–18 ]…”
Section: Introductionmentioning
confidence: 99%
“…
Os(II) complexes given the low price, minor environmental pollution, and abundant resource of copper. [1][2][3][4][5][6][7][8][9][10][11][12][13] Owing to the rich coordination chemistry of Cu(I) ions, their combination with organic and inorganic ligands often leads to a large structural diversity, ranging from discrete molecular 0D to 1D chains, and from 2D layers to extended 3D networks. [14][15][16][17][18] Generally, luminescent Cu(I) hybrid materials can be synthesized via the reaction of CuX with organic nitrogen, phosphorus, and sulfur ligands in organic solvents.
…”
mentioning
confidence: 99%
“…[8][9][10][11][12] Such cuprous complexes show great potential for applications in optoelectronic devices and luminescencebased sensors. [13][14][15][16][17] The d 10 configuration of Cu(I) tends to favor the tetrahedral geometry and extensive studies on Cu(I)-based emitters show that the typical mononuclear four-coordinated Cu(I) complexes generally exhibit inferior luminescence properties. 18,19 This is associated with the nature of the low oxidation potential of the Cu + ion, which results in significant metal-to-ligand charge transfer (MLCT) excited states.…”
Section: Introductionmentioning
confidence: 99%